Analisis Dampak Rehabilitasi Jaringan Irigasi Tersier Terhadap Pendapatan Petani Di Kabupaten Aceh Besar - Evariani, E (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2018)
The function of the irrigation is very important in agriculture system. Irrigation is utilized by farmers particularly rice farmers to irrigate and maintain the adequacy of water in their rice fields. Since the first of the irrigation system has developed, the different in quality and system managements still, Aceh Besar regency has an area of 31,998.0 Ha of rice fields and the land that have irrigation scope are 20,275 Ha. With the irrigation rehabilitation programs becoming more eficient in rice production and farmers income are increasing therefore the researce on the analysis of impact the rehabilitation of tertier irrigation on farmers income and an analysis of the breakeven point (BEP) in Aceh Besar regency conducted. This research was conducted with a purposive sampling method (deliberately) based on the consideration of farmers around the location of the study received support rehabilitation of irrigation tertiary fund budget for fiscal year 2016 for data analysis using quantitative approaches such as analysis of t test, R / C ratio and analysis of breakeven point.